2020
DOI: 10.1002/pdi.2294
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease and cardiovascular outcomes in COVID‐19

Abstract: Patients with cardiovascular disease have an increased risk of severe COVID‐19 disease and an increased mortality. Clinical observations have described cardiovascular complications of COVID‐19 in patients without prior cardiovascular disease, including acute cardiac injury, myocarditis, heart failure, arrhythmias, and acute coronary syndromes. These are also associated with a worse outcome from COVID‐19. Several of the potential treatments for COVID‐19 may also have cardiovascular consequences. Some of the acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Singh et al, in a meta-analysis revealed that the CVDS increased the risk of mortality in patients SARS-COV-2 infection [18]. A study in Hubei province among 44 672 confirmed cases with COVID-19 reported that infected patients without any underling disease had a case fatality rate of 0.9 %, rising to 6 % in patients with hypertension, 7 % in patients with diabetes and 10 % in patients with CVDs [63]. Momtamanesh et al, in meta-analysis based on 35 studies revealed that CVDs occurred in more than 25 % of infected cases with SARS-COV-2, mortality was 20 times higher, and admission to ICU increased by 13.5 times.…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al, in a meta-analysis revealed that the CVDS increased the risk of mortality in patients SARS-COV-2 infection [18]. A study in Hubei province among 44 672 confirmed cases with COVID-19 reported that infected patients without any underling disease had a case fatality rate of 0.9 %, rising to 6 % in patients with hypertension, 7 % in patients with diabetes and 10 % in patients with CVDs [63]. Momtamanesh et al, in meta-analysis based on 35 studies revealed that CVDs occurred in more than 25 % of infected cases with SARS-COV-2, mortality was 20 times higher, and admission to ICU increased by 13.5 times.…”
Section: Discussionmentioning
confidence: 99%
“…The CHA 2 DS 2 -VASc score is note-worthy since it does not require any biochemical markers or radiography, and requires basic knowledge of cardiovascular medical history, along with age and sex. The presence of hypertension, diabetes, congestive cardiac failure, previous ischaemic heart disease, and stroke which increase the CHA 2 DS 2 -VASc score have been strongly associated with adverse outcomes in patients with COVID-19 [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…3. Comorbidities: Given that patients with cardiovascular comorbidities are at higher risk of severe disease and mortality (28), it is natural to consider the cardiovascular information that is also contained in thoracic CT. Models that incorporate automated calcium scoring, for example, allow for the burden of atherosclerotic disease to be incorporated into prognostic models, even in those patients with no prior cardiovascular diagnosis. The effects of COVID-19 on the heart have received little attention.…”
Section: Thoracic Ctmentioning
confidence: 99%